Population and vegetation structure of ramin (Gonystylus bancanus) in secondary forests of Ketapang District, West Kalimantan, Indonesia - ABDURRANI MUIN; DWI ASTIANI (Biodiversitas Journal of Biological Diversity, 2018)
Muin A, Astiani D. 2018. Population and vegetation structure of ramin (Gonystylus bancanus) in secondary forests of Ketapang District, West Kalimantan, Indonesia. Biodiversitas 19: 528-534. In the tropical peatland, ramin (Gonystylus bancanus Miq. Kurz) was one of many prominent species that present in peatland forest. The species distribution is mostly in Southeast Asia peatland. The beautiful wood color, pale yellow sometimes grayish with no differentiated sapwood and heartwood with straight interlocked grain, made it become the most wanted tree species from tropical peatland.The exploitation of Ramin wood since the 1970s caused the decrease of its population in the peatland forest, led to this species being listed as an endangered species. This study aimed to search information on the Ramin population and vegetation structure left in its habitat in secondary peatland forest of Pematang Gadung and Sungai Sirih villages area of Ketapang District. The study employed a survey method, and data collection was carried out using line plots system. Data assessed were natural regeneration condition-seedling, sapling and pole growth levels-, and tree growth levels. A 20 m x 20 m size plots were continually established to form a line with the length of 550-680 m. Results showed that relatively a few Ramin was found in the forests in Sungai Sirih with a mean seedling density of only 9.9 tree ha-1, height ranges of 131 cm to 150 cm, and counted sapling level of 183 trees ha-1 with diameter ranges from 0.38 to 6.37 cm. At Pematang Gadung village, more Ramin was found, especially with a bigger diameter. Tree level (diameter >20cm) was recorded at 74.1 tree ha-1 with a contradictory far less seedling (2.8 tree ha-1), sapling level (only 1 tree ha-1) and pole level (7.4 tree ha-1) established. Based on the tree population condition and the variation of their growth level, the vegetation structure of Ramin did not describe a normal curve form in the natural forest both in the villages of Pematang Gadung and Sungai Sirih.